La libertà religiosa alla prova del Covid-19. Asimmetrie giuridiche nello “stato di emergenza” e nuove opportunità pratiche di socialità (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Breve premessa orientativa - 2. Verso dove convergere - 3. Il nuovo statuto della solidarietà - 4. Rinnovate pratiche di relazioni sociali: il laboratorio della libertà religiosa - 5. Socializzare i diritti/espandere le libertà - 6. Il test della libertà religiosa in tempi di Coronavirus - 7. Fare tesoro dell’esperienza, modulare le risposte, organizzare il futuro.Religious freedom and the challenge of Covid-19. Legal asymmetries in the “state of emergency” and new opportunities for social actorsABSTRACT: The essay develops some concrete, both legal and political, analyses concerning the relationship between the Covid-19 pandemic and the fundamental right of religious freedom. The "state of emergency" that came about and the consequent decisions taken by the government to contain the spread of the coronavirus, have put pressure on certain fundamental freedoms and rights of both individuals and social formations, including religious freedom - according to some, more compressed from the point of view of its practical expressions. The question arises of how much, in the mid-long term, such measures will affect the structure of relations between the State and religious confessions and, more generally, religiosity as a sentiment widespread at societal level.